Pengaruh Kegiatan Wisata Terhadap Perubahan Penggunaan Lahan Di Kecamatan Tawangmangu, Kabupaten Karanganyar - Yuki Riswandha; Hadi Wahyono (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Karanganyar is one of regency in Central Java province which it’s potential tourist destinations are quite diverse. Nature destinations is one of the tourism assets which commonly found in Karanganyar, facts shown that the existing landscape conditions vary widely from highland terrain to the landscape of coastal lowland forest. Tourism sector contributes in a significance economic scale towards local incomes of Karanganyar Regency. One district which became the center of tourism activities development is Tawangmangu. Tawangmangu district has an integrated tourism destination named Kawasan Wisata Tawangmangu, which consist of several tourism place option like Grojogan Sewu Waterfall, Sapta Tirta, Campgrounds Sekipan, and Taman Ria Balekambang. Because it is the main area of tourism destination in Karanganyar, adequate infrastructure is available and regularly upgraded in the annual basis, because those improvements is needed to support massive tourism activities which might occurred. With the tourism activities development such as newly constructed infrastructure or addition of a few supporting facilities will certainly give effect to the land use transformation of those aforementioned surroundings. This study aimed to analyze the effects of tourism activities towards land use transformation and analyze the causes of changes regarding land use in the Tawangmangu District. In the process of answering these objectives, this study used descriptive qualitative approach. Research on the effects of tourism activities is based on four main analysis, which is tourism characteristic activities, land use transformation, effects of tourism activities towards land use transformation, and the causes of effect of land use transformation. From those four baseline analysis, result shows that tourism activities which has been occurred so far only affects certain areas of Kalisoro, Tawangmangu, and Blumbang. As for the case of land use transformation, in other villages they are not affected by the existence of tourism activities. Besides tourism, land use transformation in the Tawangmangu District also caused by environmental quality, land values, accessibility, also availability of basic decent facilities and infrastructure.